2020
DOI: 10.1108/jhr-11-2019-0243
|View full text |Cite
|
Sign up to set email alerts
|

Reliability and validity of a post-traumatic checklist-5 (PCL-5) among fire and rescue officers in Selangor, Malaysia

Abstract: PurposeThis study is to establish the validity and reliability of Malay version of Post-traumatic Check List-5 (MPCL-5) among the fire and rescue officers in the state of Selangor, Malaysia.Design/methodology/approachA cross-sectional study was conducted, which involved 100 firefighters from the state of Selangor, Malaysia. Construct validity, internal consistency, and concurrent validity were performed and analyzed using Statistical Package for Social Sciences (SPSS) version 20. Concurrent validity was tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
2
2
0
Order By: Relevance
“…Internal consistency measures for the PCL-5 (𝞪 = 0.94), PHQ-9 (𝞪 = 0.87), and GAD-7 (𝞪 = 0.92) were all high and consistent with other investigations [55,[59][60][61]. Mean reporting scores stratified by demographic characteristics are presented in Table 1.…”
Section: Mental Disorder Symptom Clusterssupporting
confidence: 76%
“…Internal consistency measures for the PCL-5 (𝞪 = 0.94), PHQ-9 (𝞪 = 0.87), and GAD-7 (𝞪 = 0.92) were all high and consistent with other investigations [55,[59][60][61]. Mean reporting scores stratified by demographic characteristics are presented in Table 1.…”
Section: Mental Disorder Symptom Clusterssupporting
confidence: 76%
“…Internal consistency measures for the PCL-5 (𝞪 = 0.94), PHQ-9 (𝞪 = 0.87), and GAD-7 (𝞪 = 0.92) were all high and consistent with other investigations [53,[57][58][59]. Mean reporting scores stratified by demographic characteristics are presented in Table 1.…”
Section: Mental Health Outcomessupporting
confidence: 76%
“…The results of the studies on trauma-exposed college students [60] and US veterans [61] indicated good internal consistency, satisfactory reliability, and significant correlations with measures of other constructs (convergent and discriminant validity). Also, the first validation study of the Malay version of a PCL-5 for Malaysian fire and rescue officers demonstrates a valid and reliable scale for screening probable PTSD diagnosis [62]. However, it seems that the results of the current research follow the related studies on other populations who experienced traumatic events.…”
Section: Plos Onementioning
confidence: 51%